Non-Conventional Yeasts as a Source of Genetic Diversity and Biotechnological Potential - Cubillos-Riffo, F (2025)
Most of our current knowledge about yeast is based on the workhorse Saccharomyces cerevisiae. However, can this yeast represent the vast array of natural yeast life-forms? This review discusses significant recent advances in the study of non-Saccharomyces yeasts, also known as non-conventional yeasts (NCYs). We (a) review recent literature on bioprospecting methodologies and on population genomics that have expanded our understanding of NCY diversity, (b) highlight critical species with industrial applications, and (c) offer insights into how NCYs genetic diversity translates into phenotypic plasticity and adaptation to extreme environments. We assess the limitations that are delaying the widespread use of NCYs in biotechnology, including the need for ambitious bioprospecting efforts and robust genetic tools in the scaling up of NCY-based processes for industry. NCYs could offer novel sustainable solutions in the food, beverage, pharmaceutical, and bioenergy sectors and could open a new frontier of commercial opportunities.